Conditions of Lawfulness for Causing Harm to Interests Protected by Criminal Law in The Course of Conducting an Operational-Search Measure - Barseghyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2025)
In order to establish the applicability of any circumstance excluding criminal liability, the existence of the conditions of lawfulness for that circumstance must be confirmed. In this article, we examine the conditions of lawfulness for the circumstance excluding criminal liability, which we have proposed under the title “Causing Harm to Interests Protected by Criminal Law in the Course of Conducting an Operational-Search Measure”. As a result of the study of the proposed content of this circumstance excluding criminal liability, the following conditions of lawfulness have been identified, the essence of which is examined in detail in separate sections of this article: • harm to interests protected by criminal law must be caused in the course of conducting an operational-search measure, • the harm must be caused by a person conducting operational-search activity in accordance with the procedure established by law, • the harm must be caused within the scope of an assignment given for the purpose of preventing or detecting a crime, or obtaining evidence, • there must be no alternative measures unrelated to causing harm that could achieve the intended purpose, • the limits of causing lawful harm must be maintained during the conduct of the operational-search measure. Only in the presence of all the listed conditions simultaneously can the existence of the circumstance excluding criminal liability under consideration be confirmed. Based on the results of the research conducted, the article presents a number of proposals of scientific and practical value.